Odwrócony „świat na opak”. O Masce Śmierci Szkarłatnej Edgara Allana Poe w kontekście teorii karnawału - Górka, Elżbieta; Wandowicz, Mieszko (Przestrzenie Teorii, 2021)
This paper considers The Masque of the Red Death, a short story by E.A. Poe. Understanding the carnival as mundus inversus (temporary inversion of order) and using the theories proposed by M. Bakhtin or V. Turner, the authors present an interpretation according to which Poe’s ball is indeed an inversion of a ball – an anti-carnival. Furthermore, they do not agree with the allegorical understanding of Poe’s works. Indicating a suggestion made by Poe himself, they choose an interpretation related to Eliade’s concept of symbolism. They also disagree with the theory in which The Masque of the Red Death is the story about the non-existence of God. Referring to other religious interpretations and the problems of time, they present their own biblical conclusion.